Substantial variation in larval honey bee nutrition within and among Apis mellifera colonies - Rebecca R. Westwick; Clare C. Rittschof (PLoS ONE, 2026)
Parents have evolved strategies to reduce the risk of malnutrition in offspring, including the production of specialized nutritional secretions that are tailored to meet the unique needs of developing offspring. Studies in vertebrates, however, show abundant individual variation in nutritional secretions; the causes and consequences of this variation, and the extent to which such patterns can be generalized beyond vertebrates, remain unclear. Here, we investigated natural variation in nutritional secretions in an invertebrate species, the Western honey bee ( Apis mellifera L.). This is a unique bee wherein developing larvae subsist entirely on “jellies” (e.g., royal jelly) produced by glands in adult worker bees. We assess within- and among-colony variation in the macronutrient content of the secretions fed to female worker larvae (“worker jelly”), collected from individual larval honeycomb cells. Although female workers make up the largest demographic inside a honey bee colony, very few studies have investigated their larval diet; even fewer have included the scope of colonies needed to assess natural variation in this critical nutritional substance. In one of the largest such studies to date, we found significant variation both within and among colonies in total quantity and macronutrient content of worker jelly, but with greater variation among colonies; this pattern was strongest for proteins. We further assessed whether worker jelly composition was correlated with colony defensive aggression because of extensive links between aggression, foraging activity, and larval development outcomes; however, we observed no such relationship. This study is a critical step in understanding the evolution and maintenance of offspring provisioning strategies, as well as bee foraging ecology and nutritional stress response.